Case Report: Efficacy of anlotinib and sintilimab in treating lung adenocarcinoma with RET fusion and PD-L1 expression - Bao, Hejing; Zhang, Jiani; Wang, Yuhuan; Chen, Zhiting; Luo, Xi; Li, Ting; Su, Haoran; Bao, Hehong; Cao, Xiaolong; Lin, Liping (Frontiers in Pharmacology, 2024)
We report a case of an advanced non-small cell lung cancer (NSCLC) patient with brain metastasis, RET fusion, and high expression of programmed death ligand 1 (PD-L1) at initial treatment. After receiving radiotherapy for the brain metastasis, the patient started with anlotinib and added immunotherapy with sintilimab. The patient had a good response to anlotinib and sintilimab treatment, tolerated the adverse reactions, and had a progression-free survival(PFS) of over 17 months. To the best of our knowledge, this is the first clinical case report in the literature describing the benefit of anlotinib and sintilimab treatment for non-small cell lung cancer with RET fusion and high PD-L1 expression. This study explores the biomarker selection for targeted therapy and combined immunotherapy in NSCLC patients.